Caracterización de la cadena logística de los pequeños productores de café en la provincia de Lengupá (2020)
The purpose of this research is to characterize the logistics chain for small coffee producers in the Province of Lengupá, department of Boyacá, identifying the different links and actors involved in coffee logistics in this province. The failures detected in its operation and the relationship that exists between each of the different actors are also described. The institutional support offered by state entities and non-governmental organizations for the promotion of coffee cultivation is evaluated. When evaluating the effects of intermediation by product marketers in the study area, it is noted that they are not significant for an efficient performance of the logistics chain. The development of this project took place in two stages, the description of the logistics chain of coffee producers, based on secondary sources of information, mainly from texts related to coffee production and academic research focused on research into the supply of the sector. coffee maker. In the second stage, emphasis was placed on describing the configuration of the logistics chain with the use of primary sources such as the survey and interview that were carried out with coffee producers and marketers.